SIKLUS PENDAPATAN DAN PENGELUARAN KAS DI TOKO EMAS E TARGER DALAM SISTEM INFORMASI AKUNTANSI - Sihombing, Yohanna Paulina; Hutapea, Marlyna Infryanty; Elisabeth, Duma Megaria (Universitas Methodist Indonesia, 2023)
This study aims to examine the income and expenditure cycle at the E Targer Gold Shop with an accounting information system. The use of accounting information systems helps improve efficiency and accuracy in the cycle process. This study uses a descriptive method by collecting data through observation, interviews, and analysis of related documents. Several problems were found that could be corrected through the implementation of an accounting information system. In the revenue cycle, the information system makes it easier to record sales and financial reports. In the expenditure cycle, the information system facilitates the procurement and recording of expenditures. Implementation of accounting information systems is recommended to increase efficiency, accuracy, and make the right decisions in a gold shop.